Myth or reality? Some directions on translation universals in recent corpus based case studies - Jia, Juan; Afzaal, Muhammad; Naqvi, Swaleha Bano (Frontiers in Psychology, 2022)
This paper contributes to the ongoing debate on the existence of translation universals (TUs) by mapping the theoretical literature on the TUs and evaluating selected corpus-based studies which investigate a swath of hypothesized universals. Based on a review of empirical research carried out over recent years in translation studies, this paper attempts to develop a holistic picture of the evidence on TUs pertaining to multiple aspects of translation. We found that although some evidence for certain hypothesized universals exists, it cannot be definitively claimed that TUs comprise an indisputable reality. Based on review of the studies surveyed, the present study concluded that several universal claims within research, over the period of time, proved to have been falsified at a universal level, while being proved right as lower-level translation modes or determined generalizations for particular types. Thus as the hypotheses regarding universals have been worked upon on a very small range of languages or pair of languages, it is imprudent to declare them as translation universals.